Anti-hyperuricemia effect of hesperetin is mediated by inhibiting the activity of xanthine oxidase and promoting excretion of uric acid - An, Meng-Fei; Shen, Chang; Zhang, Shao-Shi; Wang, Ming-Yue; Sun, Ze-Rui; Fan, Mao-Si; Zhang, Li-Juan; Zhao, Yun-Li; Sheng, Jun; Wang, Xuan-Jun (Frontiers in Pharmacology, 2023)
Hesperetin is a natural flavonoid with many biological activities. In view of hyperuricemia treatment, the effects of hesperetin in vivo and in vitro, and the underlying mechanisms, were explored. Hyperuricemia models induced by yeast extract (YE) or potassium oxonate (PO) in mice were created, as were models based on hypoxanthine and xanthine oxidase (XOD) in L-O2 cells and sodium urate in HEK293T cells. Serum level of uric acid (UA), creatinine, and urea nitrogen were reduced significantly after hesperetin treatment in vivo. Hesperetin provided hepatoprotective effects and inhibited xanthine oxidase activity markedly, downregulated the protein expression of XOD, toll-like receptor (TLR)4, nucleotide binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, and interleukin-18 in a uric acid-synthesis model in mice. Protein expression of organic anion transporter 1 (OAT1), OAT3, organic cationic transporter 1 (OCT1), and OCT2 was upregulated by hesperetin intervention in a uric acid excretion model in mice. Our results suggest that hesperetin exerts a uric acid -lowering effect by inhibiting xanthine oxidase activity and protein expression, intervening in the TLR4-NLRP3 inflammasome signaling pathway, and upregulating expression of OAT1, OAT3, OCT1, and OCT2 proteins. Thus, hesperetin could be a promising therapeutic agent against hyperuricemia.